Mortality burdens in California due to air pollution attributable to local and nonlocal emissions. (December 2019) - Wang, Tianyang; Zhao, Bin; Liou, Kuo-Nan; Gu, Yu; Jiang, Zhe; Song, Kathleen; Su, Hui; Jerrett, Michael; Zhu, Yifang
Highlights: Local and nonlocal emissions both significantly affect the air quality in California. Nonlocal emissions could lead to more deaths than local emissions. The impacts of emissions on PM2.5 and O3 have seasonal and spatial variations. Governments need work collaboratively to develop emission control policies. Abstract: Limited research has been conducted on the contributions of local and nonlocal emission sources to ambient fine particulate matter (PM2.5 ) and ozone (O3 ) and their associated mortality. In this study, we estimated the total mortality resulting from long-term PM2.5 and O3 exposures in California in 2012 using multiple concentration response functions (CRFs) and attributed the estimated mortality to different emission groups. The point estimates of PM2.5 -associated mortality in California ranged from 12, 700 to 26, 700, of which 53% were attributable to in-state anthropogenic emissions. Based on new epidemiological evidence, we estimated that O3 could be associated with up to 13, 700 deaths from diseases of both the respiratory and cardiovascular systems in California. In addition, 75% of the ambient O3 in California was due to distant emissions outside the western United States, leading to 92% of the O3 -associated mortality. Overall, distant emissions lead to greater mortality burdens of air pollution in California than local anthropogenic emissions.